**Problem:** Let \(0<x_1\leq x_2\ldots\leq x_{n-2}\leq x_{n-1}\leq x_n\) with \(n\geq 2\) and

\[\sum_{k=1}^n\frac{1}{x_k+1}=1.\]

Show that

\[\sum_{k=1}^n\frac{1}{\sqrt{x_k}}\leq\frac{1}{n-1}\left(\sum_{k=1}^n\sqrt{x_k}\right).\]

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestSolution:It suffices to show that\[n\left(\sum_{k=1}^n\frac{1}{\sqrt{x_k}}\right)\leq\sum_{k=1}^n\left(\sqrt{x_k}+\frac{1}{\sqrt{x_k}}\right),\]

or equivalently

\[n\left(\sum_{k=1}^n\frac{1}{\sqrt{x_k}}\right)\leq\left(\sum_{k=1}^n\frac{x_k+1}{\sqrt{x_k}}\right)\left(\sum_{k=1}^n\frac{1}{x_k+1}\right).\]

Consider the function \(f(x)=\sqrt{x}+\frac{1}{\sqrt{x}}=\frac{x+1}{\sqrt{x}}, x\in(0,+ \infty).\) It is easy to verify that \(f\) is non-decreasing on \((1,+\infty)\) and that \(f(x)=f\left(\frac{1}{x}\right)\) for all \(x>0.\) Furthermore, from the given conditions, it follows that only \(x_1\) can be less than \(1\) and that \(\frac{1}{x_2+1} \leq 1-\frac{1}{x_1+1}=\frac{x_1}{x_1+1}.\) Hence, \(\frac{1}{x_1}\leq x_2.\) It is now clear that (for both cases \(1\leq x_1\) and \(x<1\)) that

\[f(x_1)=f\left(\frac1{x_1}\right) \leq f(x_2)\leq \ldots \leq f(x_n).\]

This means that the sequence \(\left(\frac{x_k+1}{x_k}\right)_{k=1}^n\) is non-decreasing. Thus, by Chebyshev's inequality, we have

\[n\left(\sum_{k=1}^n\frac{1}{\sqrt{x_k}}\right)\leq\left(\sum_{k=1}^n\frac{x_k+1}{\sqrt{x_k}}\right)\left(\sum_{k=1}^n\frac{1}{x_k+1}\right),\]

and we are done.

Equality is attained if and only if \(\frac{1}{x_1+1} = \ldots = \frac{1}{x_n+1},\) or \(\frac{x_1+1}{\sqrt{x_1}}=\ldots = \frac{x_n+1}{\sqrt{x_n}},\) which implies that \(x_1=x_2=\ldots=x_n.\) Thus equality holds if and only if \(x_1=x_2=\ldots=x_n=n-1._\square\)

Log in to reply